Student’s Perceptions of Using Songs in Learning English Vocabulary of Eighth Grade Students at SMP Cinta Rakyat 3 Pematangsiantar - Agnes Gau Densia Bulu; Bernieke Anggita Ristia Damanik; Bobby Pramjit Singh Dhillon (International journal of technology and education research, 2026)
This study aims to investigate students’ perceptions of using songs in learning English vocabulary among eighth-grade students at SMP Cinta Rakyat 3 Pematangsiantar. Vocabulary is a fundamental component in English language learning, yet many students still face difficulties in mastering it due to limited motivation and the use of conventional teaching methods. Therefore, this study explores the use of songs as an alternative learning medium to support vocabulary acquisition. This research employed a descriptive qualitative design. The participants were students of class VIII-B who had experienced learning English vocabulary through songs. The data were collected using a questionnaire and semi-structured interviews. The questionnaire results were analyzed using descriptive statistics, while the interview data were analyzed thematically to support the quantitative findings. The results show that students generally have positive perceptions toward the use of songs in learning English vocabulary. Songs help students memorize vocabulary more easily through repetition and rhythm, increase learning motivation, and create an enjoyable classroom atmosphere. In addition, songs encourage students to be more active in class and develop independent learning habits such as listening to songs outside the classroom and practicing pronunciation. Although some students faced minor difficulties such as fast song tempo and unclear pronunciation, these challenges did not significantly reduce their positive perceptions. Overall, the study concludes that songs are an effective and engaging medium for teaching English vocabulary. The use of songs can improve students’ vocabulary mastery while also increasing their motivation and participation in learning activities.